LEADERSHIP TRAINING FOR ORPHANAGE STUDENTS: MAKE THE ORPHANAGE A PLACE TO FORGE LEADERSHIP CHARACTER - Muammar Khaddafi; Mursidah; Irada Sinta; Muhammad Multazam; Sari Yulis Terfiadi; Jumadiah (RADJA PUBLIKA, 2025)
This study examined the impact of a leadership training program on children living in an orphanage. Using a participatory action research approach, the program aimed to improve the character and leadership skills of 30 children aged 12-18 years. Interactive methods, including lectures, role-plays, simulations, and group discussions, were used over three days. Data were collected through pre- and post-tests, direct observation, and in-depth interviews. The results showed significant improvements in the participants’ knowledge, attitudes, and leadership skills. The training also fostered increased self-confidence, initiative, and empathy among the children. These findings highlight the potential of orphanages as strategic venues for leadership development. The study concluded that leadership training can have a positive impact on the character and soft skills of children in orphanages, equipping them with the tools necessary to become future leaders and responsible members of society.